EVALUASI PENGENDALIAN INTERNAL DALAM PENGELOLAAN SISTEM PENERIMAAN DAN PENGELUARAN KAS PADA PT CENTRAL PRIMA SUKSES - Eny, Eny; Efriyenti, Dian (Universitas Sam Ratulangi, 2020)
PT. Central Prima Sukses is currently lacking in oversight of receivables and inventory company, the system is ineffective use and the supplier often don’t give the proof of cash receipt to company. This study has the aim to analyze internal control and constraints in receipt and disbursements cash at company. This study uses descriptive qualitative methods that are supported by observation, documentation, and interviews. The population use is all company have and the sample use is all document about transaction purchases and sales transaction. The results of this study is bad debts and the amount of inventory has differences at system and the physical inventory is caused by a lack of human resources, information system uneffectiive because Still using Microsoft excel to help the main system accurate, the system receipt and disbursement cash in accordance with the company predeterminded cycle, documents used as proof of the cash receipts and the payments for ease work of employees, but there are suppliers who do not give it , the division of responsibilities to employees has been going well, and accounting records like a journal for system receipt and disbursements on company. Keywords: Cash Disbursements System; Cash Receipt System; Internal Control